2017
DOI: 10.1088/1674-1137/41/7/074102
|View full text |Cite
|
Sign up to set email alerts
|

system

Abstract: Using local central Yukawa-type Malfliet-Tjon interactions reproducing the low-energy parameters and phase shifs of the nn system and the latest updates of the nΛ and ΛΛ Nijmegen ESC08c potentials we study the possible existence of a 4 ΛΛ n bound state. Our results indicate that the 4 ΛΛ n is unbound, being just above threshold. We discuss the role played by the 1 S 0 nn repulsive term of the Yukawa-type Malfliet-Tjon interaction.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…However, in a recent calculation using the stochastic variational method in a pionless effective field theory approach [3], it has been concluded that the ΛΛnn system is unbound by a large margin. We had previously come to the identical conclusion [4] in a study of the uncoupled ΛΛnn system using local central Yukawa-type Malfliet-Tjon interactions reproducing the low-energy parameters and phase shifts of the nn system and the latest updates of the nΛ and ΛΛ Nijmegen ESC08c potentials. It is important to notice that in order to create a ΛΛnn bound state the four particles must coincide simultaneously since the system does not contain two-or three-body subsystem bound states, so that the probability of the event occurring is rather small.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…However, in a recent calculation using the stochastic variational method in a pionless effective field theory approach [3], it has been concluded that the ΛΛnn system is unbound by a large margin. We had previously come to the identical conclusion [4] in a study of the uncoupled ΛΛnn system using local central Yukawa-type Malfliet-Tjon interactions reproducing the low-energy parameters and phase shifts of the nn system and the latest updates of the nΛ and ΛΛ Nijmegen ESC08c potentials. It is important to notice that in order to create a ΛΛnn bound state the four particles must coincide simultaneously since the system does not contain two-or three-body subsystem bound states, so that the probability of the event occurring is rather small.…”
Section: Introductionmentioning
confidence: 60%
“…On the other hand, this is reasonable because if the mixed symmetric radial wave function of the three neutrons would not penalize the interaction, the 4 H ≡ pnnn would be bound in nature due to the stronger pn interaction. However, no 4 H positive parity level has ever been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following a suggestion made by Avraham Gal, they explored the conjecture that decays of a n double hypernucleus may be responsible for some of the observed structures in the correlated momenta. However, in a recent calculation using the stochastic variational method in a pionless effective field theory approach [3], it has been concluded that the system is unbound by a large margin. We had previously come to the same conclusion [4] in a study of the uncoupled system using local central Yukawa-type Malfliet-Tjon interactions reproducing the low-energy parameters and phase shifts of the system and the latest updates of the and ΛΛ Nijmegen ESC08c potentials.…”
Section: Introductionmentioning
confidence: 99%
“…12 Following a suggestion made by Avraham Gal, they explored the conjecture that decays of a 4 ΛΛ n double hypernucleus may be responsible for some of the observed structures in the correlated π − − π − momenta. A couple of theoretical groups 13,14 have discussed the possibility that a bound state may exist in the ΛΛnn system. In particular, Ref.…”
Section: Introductionmentioning
confidence: 99%